(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Culture is an essential product of legacy of mankind and thus constitutes the “universal customs and traditions of humankind. It is the wisdom of our ancestor’s knowledge on which our present is based. It is that knowledge which is continuously contributing to the social, economic and cultural growth of state. It is the traditional knowledge of cultural expressions with which a community or a group is identified and a nation’s development is associated. Today, this knowledge is plundered and is subjected to unwarranted exploitation by the people outside the community due to globalisation and digitalization, thus, endangering the existence of the culture and community holding this cultural knowledge. Considering, this there is pertinent need to protect and preserve these cultural expression. In order to uphold the dignity, identity and respect for the culture and associated social, economic and cultural growth of a nation.